2014
DOI: 10.1073/pnas.1405266111
|View full text |Cite
|
Sign up to set email alerts
|

CHD8 regulates neurodevelopmental pathways associated with autism spectrum disorder in neural progenitors

Abstract: Truncating mutations of chromodomain helicase DNA-binding protein 8 (CHD8), and of many other genes with diverse functions, are strong-effect risk factors for autism spectrum disorder (ASD), suggesting multiple mechanisms of pathogenesis. We explored the transcriptional networks that CHD8 regulates in neural progenitor cells (NPCs) by reducing its expression and then integrating transcriptome sequencing (RNA sequencing) with genome-wide CHD8 binding (ChIP sequencing). Suppressing CHD8 to levels comparable with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
360
4
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(415 citation statements)
references
References 53 publications
(63 reference statements)
37
360
4
7
Order By: Relevance
“…Ikaros-NuRD subunit CHD4 has a role in thymocyte development (Arenzana et al, 2015;Sridharan and Smale, 2007) NuRD has roles in cardiomyocyte proliferation (Garnatz et al, 2014) and in renal progenitor cells during kidney development (Denner and Rauchman, 2013) CHD5 CHD5 Orchestrates chromatin remodeling during neurogenesis (Thompson et al, 2003;Vestin and Mills, 2013) and sperm development ) CHD7 CHD7 Involved in charge syndrome (Bajpai et al, 2010;Janssen et al, 2012;Vissers et al, 2004), neurogenesis (Hurd et al, 2010), adult brain development (Jones et al, 2015), cardiac development (Payne et al, 2015), and proper craniofacial and tracheal development (Sperry et al, 2014) CHD8 CHD8 Involved in autism spectrum disorder (Sanders, 2015) and neural development (Bernier et al, 2014;Cotney et al, 2015;Sugathan et al, 2014) CHD9 CHD9 Associates with selective promoters of osteoprogenitors (Shur et al, 2006) *Current mouse gene symbols are listed only where they differ from protein nomenclature.…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikaros-NuRD subunit CHD4 has a role in thymocyte development (Arenzana et al, 2015;Sridharan and Smale, 2007) NuRD has roles in cardiomyocyte proliferation (Garnatz et al, 2014) and in renal progenitor cells during kidney development (Denner and Rauchman, 2013) CHD5 CHD5 Orchestrates chromatin remodeling during neurogenesis (Thompson et al, 2003;Vestin and Mills, 2013) and sperm development ) CHD7 CHD7 Involved in charge syndrome (Bajpai et al, 2010;Janssen et al, 2012;Vissers et al, 2004), neurogenesis (Hurd et al, 2010), adult brain development (Jones et al, 2015), cardiac development (Payne et al, 2015), and proper craniofacial and tracheal development (Sperry et al, 2014) CHD8 CHD8 Involved in autism spectrum disorder (Sanders, 2015) and neural development (Bernier et al, 2014;Cotney et al, 2015;Sugathan et al, 2014) CHD9 CHD9 Associates with selective promoters of osteoprogenitors (Shur et al, 2006) *Current mouse gene symbols are listed only where they differ from protein nomenclature.…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 99%
“…Furthermore, CHD7 is required for neurogenesis during inner ear morphogenesis (Hurd et al, 2010). CHD8, in contrast, is linked to autism spectrum disorder (ASD); reducing the Chd8 dose by half in neural progenitors downregulates genes involved in neural development, including those associated with ASD (Sugathan et al, 2014). CHD proteins are also involved during heart development.…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 99%
“…While the minimal deleted region contains CHD8 and the adjacent SUPT16H locus, the importance of abrogated CHD8 function in the phenotype of these patients is underscored by the identification of disruptive CHD8 mutations in individuals with DD or ASD [31] and recapitulation of a subset of features of the human phenotype in the zebrafish model [32]. Although other CHD proteins have yet to be linked to human genetic disease, it has been demonstrated that CHD4 and CHD5 carry out important functions in neurogenesis [33,34].…”
Section: Chd Family and Genetic Diseasementioning
confidence: 99%
“…CHD proteins in autism spectrum disorder, intellectual disability, and epilepsy Application of cytogenetic and next-generation sequencing technologies to large cohorts of individuals with autism spectrum disorder (ASD), intellectual disability (ID), and/or epilepsy has uncovered de novo and inherited heterozygous frameshift, nonsense, or copy dosage mutations in several CHD genes, including CHD2, CHD6, CHD7, and CHD8 [66][67][68][69][70][71][72][73][74]. For CHD2, CHD6, and CHD7, mutations identified thus far are nonrecurrent (present in only individual cases), private mutations that account for a small fraction of ASD/ ID/epilepsy cases.…”
Section: Chd Proteins In Human Diseasementioning
confidence: 99%
“…In cultured cells, CHD8 has been shown to bind CHD7 and to both bind and regulate p53 and inhibit its proapoptotic effects during development; thus, it is surprising that loss of CHD8 is not associated with broader phenotypic effects in humans [79][80][81][82]. Knockdown of Chd8 by shRNA does not alter the morphology or neural ectodermal markers of neural progenitors derived from human iPS cells, but does significantly impair their gene expression [74]. A very recent study also showed that CHD7 binds to and represses p53, suggesting some CHD proteins (at least those in the third subclass) may share common downstream mechanisms, interacting factors, and target genes [83].…”
Section: Chd Proteins In Human Diseasementioning
confidence: 99%